An Improved PEG‐Linked Solid Support for Minimizing Process‐Related Impurities During Solid‐Phase Synthesis of DNA and RNA Sequences. Issue 5 (4th May 2021) - Grajkowski, Andrzej; Takahashi, Mayumi; Cawrse, Brian M.; Beaucage, Serge L.
Abstract: The preparation of controlled pore glass (CPG) supports, functionalized with several hexaethylene glycol spacers, to alleviate the problems associated with the porosity of commercial CPG supports is described in this article. The pore size of CPG restricts the diffusion of reagents to the leader nucleoside embedded in porous supports; this inhibits efficient solid‐phase syntheses of DNA and RNA sequences and, by default, the purity of those sequences through formation of a shorter than full‐length oligonucleotide. Functionalization of a CPG support with five hexaethylene glycol spacers led to a 42% reduction in process‐related impurities contaminating oligonucleotide sequences, compared to that obtained using the commercial long‐chain alkylamine (LCAA) CPG support. © 2021 Wiley Periodicals LLC. This article has been contributed to by US Government employees and their work is in the public domain in the USA. Basic Protocol 1 : Preparation of the hydroxylated CPG support 3 Basic Protocol 2 : Automated preparation of the CPG support 6 Basic Protocol 3 : Automated preparation of the poly(hexaethylene glycol)‐derived CPG 7 Basic Protocol 4 : Automated functionalization of the poly(hexaethylene glycol)‐derived CPG support 7 with leader deoxyribo‐ and ribonucleosides to provide the CPG support 9 Basic Protocol 5 : Automated syntheses of DNA and RNA sequences on poly(hexaethylene glycol)‐derived CPG support 9 and on a commercial long‐chain alkylamine (LCAA) CPG support Support Protocol : Release and deprotection of the DNA and RNA sequences linked to the poly(hexaethylene glycol)‐derived CPG support 10 and commercial LCAA‐CPG support Basic Protocol 6 : Comparative RP‐HPLC analyses of crude, fully deprotected DNA or RNA sequences released from the poly(hexaethylene glycol)‐derived CPG support 10 and from a commercial LCAA‐CPG support